Engineering isoprene synthesis in cyanobacteria. Issue 12 (27th April 2018) - Chaves, Julie E.; Melis, Anastasios
Abstract : The renewable production of isoprene (Isp) hydrocarbons, to serve as fuel and synthetic chemistry feedstock, has attracted interest in the field recently. Isp (C5 H8 ) is naturally produced from sunlight, CO2 and H2 O photosynthetically in terrestrial plant chloroplasts via the terpenoid biosynthetic pathway and emitted in the atmosphere as a response to heat stress. Efforts to institute a high capacity continuous and renewable process have included heterologous expression of the Isp synthesis pathway in photosynthetic microorganisms. This review examines the premise and promise emanating from this relatively new research effort. Also examined are the metabolic engineering approaches applied in the quest of renewable Isp hydrocarbons production, the progress achieved so far, and barriers encountered along the way. Abstract :